2017
DOI: 10.1111/ijd.13695
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in melasma: a prospective study on serum and blood markers of oxidative stress in melasma patients

Abstract: Oxidative stress was found to be increased in cases of melasma compared to the control group in this study. This substantiates the role of oxidative stress in etiopathogenesis of melasma; however, further studies are required to reach a definitive conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 30 publications
(52 reference statements)
4
36
0
1
Order By: Relevance
“…The mean age of patients at the time of presentation was 32.81 ± 6.83 years, whereas the mean age of onset based on history was 28.68 ± 6.28 years. These findings were in accordance with various previous studies . The most common pattern in our study was mixed (40%), specifically a combination of centrofacial and malar patterns, followed by centrofacial pattern (30.7%).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The mean age of patients at the time of presentation was 32.81 ± 6.83 years, whereas the mean age of onset based on history was 28.68 ± 6.28 years. These findings were in accordance with various previous studies . The most common pattern in our study was mixed (40%), specifically a combination of centrofacial and malar patterns, followed by centrofacial pattern (30.7%).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, a study conducted by Choubey et al , involving 50 cases and 50 controls, showed that the serum levels of malondialdehyde, SOD, and blood GSH‐Px were significantly higher among the cases compared to controls. Additionally, the authors also found a statistically significant positive correlation between serum malondialdehyde and severity of melasma.…”
Section: Introductionmentioning
confidence: 96%
“…The melanoma models also showed that activated Akt is implicated in MM and its invasiveness, accompanied with the elevation of mTOR, peroxides and angiogenesis [54]. In addition, an available experiment on chloasma suggested that UV-induced ROS greatly elevated the activity of tyrosinase by stimulating PI3K/Akt signaling pathway, thereby facilitating the increase of melanin [55]. Hence, blockage of this pathway to some extent would be a favourable approach for above dermatoses therapy.…”
Section: Os and Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
“…Malondialdehyde, the end-product of lipid peroxidase, can also be used to assess tissue damage due to ROS. Previous research tested the levels of these enzymes on patients with facial melasma and concluded that the levels of superoxide dismutase, catalase, glutathione peroxidase were significantly higher in melasma patients as compared to control patients (p<0.001), concluding that oxidative stress plays a role in the pathogenesis of melasma [ 11 , 12 ].…”
Section: Reviewmentioning
confidence: 99%